Kiedy dyskusja przeradza się w spór – różne odsłony programów telewizyjnych o charakterze publicystycznym w sztuce wymiany myśli i wywierania nacisków. Ujęcie genologiczne - Kalisz, Aleksandra Katarzyna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2019)
The need, already known in ancient times, to influence the interlocutor, and thus the desire to interfere in his worldview, is inseparably connected with the necessity to expose the speaking “I”, showing its own point of view. A perfect example of creating a kind of narrative about oneself and one’s own beliefs are contemporary current affairs programmes broadcast through audio and visual media. The aim of the presented article is to examine the discussion and dispute with the use of genological tools and to grasp the dichotomy between the above-mentioned constructions. Such an analysis will not only allow us to verify the thesis concerning the hybridization of both forms, but also to determine where in the television space of the studio the boundary between discussion and dispute lies and what factors determine the appearance of one of these species. The final stage of the reflection will be to look at how the environment itself, and therefore the media, can influence these forms.